22 FTY720 ENHANCEMENT OF PULMONARY ENDOTHELIAL BARRIER FUNCTION IS S1P1 RECEPTOR INDEPENDENT. (1st March 2005) - Camp, S. M.; Dudek, S. M.; Chiang, E. T.; Singleton, P. A.; Natarajan, V.; Garcia, J. G.N.
Abstract : Rationale: Disruption of pulmonary vascular integrity occurs during inflammatory disease processes such as acute lung injury and sepsis, and as a result, regulation of this barrier is an important clinical objective. We have described rapid endothelial cell (EC) barrier enhancement by the platelet-derived phospholipid, sphingosine 1-phosphate (S1P), mediated via S1P1 receptor (S1P1R) ligation. FTY720, an immunosuppressive drug currently in phase III clinical trials, is phosphorylated in vivo to form a structural analogue of S1P. We and others have demonstrated that FTY720 also induces EC barrier enhancement, and we now explore the role of S1P1R ligation in this process. Methods/Results: FTY (1 μM) significantly increased cultured human pulmonary artery EC barrier function in a sustained manner as measured by transendothelial electrical resistance (TER), with a delayed onset and slower rate of rise relative to S1P (1 μM). Lipid extraction and 2-phase thin layer chromatography studies revealed that phosphorylation of FTY is not required for barrier enhancement. Both S1P- and FTY-induced barrier enhancement were abolished by pretreatment with pertussis toxin; however, reduction of S1P1R expression via siRNA significantly inhibited S1P-, but not FTY-induced TER elevation. Both S1P and FTY rapidly (within 5 min) induced S1P1R accumulation in membrane lipid rafts, but only S1P stimulated threonine phosphorylation of S1P1R. Inhibition of this phosphorylation by preincubation with the PI3 kinase inhibitor LY294002 (10 μM) blocked S1P-, but not FTY-induced TER elevation. S1P, but not FTY, induced significant phosphorylation of ERK and myosin light chains within 5 min as detected by Western blotting and dramatic actin cytoskeletal rearrangement. Reduction of downstream effectors Rac1 or cortactin via siRNA strategies attenuated S1P-, but not FTY-induced TER elevation. Conclusion: These results indicate that FTY720 augments EC barrier function through a novel, S1P1R-independent signaling pathway. HL58064, HL70013-01, FTY720 supplied by Novartis.